2019
DOI: 10.2147/ott.s203235
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of H19 decreases the radioresistance in esophageal squamous cell carcinoma cells</p>

et al.

Abstract: Background: Radiotherapy is one of the most common treatments for esophageal squamous cell carcinoma (ESCC). Radioresistance is a major obstacle that limits the efficacy of radiotherapy. H19 has been considered as a factor affecting radioresistance, whereas the specific mechanism of H19 in ESCC radioresistance remains to be further elucidated. Purpose: The objective of this study was to identify the relationship between H19 and radioresistance. The findings are expected to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Human ESCC radiotherapy-resistant cell line KYSE150R was established by fractionated X-ray irradiation [ 28 ]. KYSE150 cells were cultured in RPMI-1640 medium (Gibco, Carlsbad, CA) containing 10% FBS (Hyclone, Logan) in a humidified incubator with 5% CO 2 (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Human ESCC radiotherapy-resistant cell line KYSE150R was established by fractionated X-ray irradiation [ 28 ]. KYSE150 cells were cultured in RPMI-1640 medium (Gibco, Carlsbad, CA) containing 10% FBS (Hyclone, Logan) in a humidified incubator with 5% CO 2 (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…This demonstrated that MALAT1 can inhibit the apoptosis induced by radiation and enhance the resistance of cells to radiotherapy, and MALAT1 silencing may enhance the sensitivity of cells to radiotherapy ( 80 ). Luo et al ( 81 ) inhibited H19 in radiation-resistant esophageal cancer cells and found an increase in miR-22-3p expression, decrease in Wnt1 expression, and reduction in cell proliferation and migration. This suggested that H19 can regulate the Wnt pathway via miR-22-3p and confer radiotherapy resistance.…”
Section: Regulation Of Long-chain Non-coding Rna Expression Can Enhan...mentioning
confidence: 99%
“…H19 was upregulated in an ESCC radioresistant cell line. And H19 knockdown downregulated Wnt1 through upregulating miR-22-3p expression, then resulted in the inhibition of radioresistance, proliferation and migration in radioresistant ESCC cell (Luo et al, 2019). Prostate cancer associated transcripts 1 (PCAT-1) was first in patients with prostate cancer by transcript sequencing and was identified as a transcriptional repressor (Prensner et al, 2011).…”
Section: Lncrnas In Esophageal Cancer Therapymentioning
confidence: 99%